Enabling the Exploration of Disorienting Dilemma in the Classroom. Issue 4 (October 2022) - DeAngelis, Lisa
While learning involves the acquisition of skills and the development of repertoires, some educators harbor even more profound learning goals, seeking to enable learning that is transformative. Theorizing about transformative learning posits that it is precipitated by a disorienting dilemma. Disorienting dilemmas may be thought of as times when new information causes a person to call into question their values, beliefs, or assumptions. Transformative learning can occur through rich, experiential learning experiences or life events, and it can also occur in the classroom. While much has been written about transformational learning, the teacher's role in the process is undertheorized.